Electrospun polyvinylpyrrolidone fibers with cobalt ferrite nanoparticles - Vinicio J. Cevallos; Sarah Briceño; Guillermo Solorzano; Jules Gardener; Alexis Debut; Raúl Dávalos; Werner Bramer-Escamilla; Gema González (Carbon Trends)
Polyvinylpyrrolidone (PVP) fibers with cobalt ferrite nanoparticles (CoFe2O4) were prepared by an electrospinning technique to study the electrical resistance and magnetic properties of the nanocomposite. The samples were characterized using Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, transmission electron microscopy (TEM), and thermogravimetric analysis (TGA). Magnetic properties were measured using vibrating sample magnetometry (VSM). PVP fibers showed an average diameter of 3.74μm with a resistance of 121.58 GΩ and 2.22μm and 1.20 GΩ with the incorporation of CoFe2O4 nanoparticles. Cobalt ferrite nanoparticles have a maximum magnetization of 81.9 emu/g, and the CoFe2O4/PVP fibers present a diamagnetic behavior with a maximum magnetization of 0.07 emu/g. Combining the versatility of PVP as a polymer matrix with the magnetic and electric properties of cobalt ferrite nanoparticles, this nanocomposite may open up new potential applications for developing electrically conductive novel nanomaterials and devices.